The role of gender in domestic water conservation in Malaysia - Chan, Ngai Weng; Vilas Nitivattananon (Environmental Management Society, Malaysia, 2007)
While the role of gender in water management is vital in many countries experiencing water scarcity, such as in the African continent and Indian Sub-continent, it is rather undefined in the case of Malaysia. This is strange considering the escalation of water problems in the country in recent decades due to climate change and social, political and economic reasons. Though the country is rich in water resources, mismanagement causes water supply to lag far behind water demand. As a result, Malaysia is facing water problems which have severe impacts, particularly on gender. This paper demonstrates that women are the main water managers both at home and in the office, and they wield tremendous influence on the ways families and businesses use and conserve water. The role of women is pivotal in curbing domestic wastage, but ensuring wise use and conservation. Since domestic consumers use roughly more than half of the country’s total water demand, Water Demand Management (WDM) is a vital conservation tool. Women are the managers of the family’s water budget. Because of the fact that women use water for most of the domestic chores in the home, they are considered vitally important in water conservation. Women also make decision on the installation of water saving devices. When women save water in the home, they also educate their children and family members about the importance of water conservation. Finally, women themselves need to cut down on water use via substitution of water-saving methods and other personal adjustments. Women who work can similarly exert their influence in the office by impressing upon colleagues and the employer about the benefits of water conservation. Overall, water conservation via involvement of the public can be effective when women are actively involved as they are the key players towards achieving sustainable management of water resources